Ralph Compton [large type] : vigilante dawn - Compton, Ralph (Galloway, Marcus. Ralph Compton novel., 2015)
Jarrett Pekoe cares about two things: his home and his family. So when rustlers kill his kin and burn his ranch to the ground, Jarrett won't rest until the men responsible have their necks in the hangman's rope. Lem Beauchamp is a stranger with a mysterious ax to grind when it comes to the bandits who razed Jarrett's ranch. Despite his suspicion of Lem, Jarrett isn't about to refuse the help of an experienced gunman. And when the hunt turns deadly, Lem and Jarrett may be the only ones willing to risk everything for justice.